Structure of the Solar Atmosphere: A Radio Perspective - Alissandrakis, Costas E. (Frontiers in Astronomy and Space Sciences, 2020)
Solar radio emission has been providing information about the Sun for over half a century. In order to fully exploit this information, one needs to have a broader view of the solar atmosphere, which cannot be provided by radio observations alone. The purpose of this review is to present this background information, which is necessary to understand the physical processes that determine the solar radio emission and to link the radio domain with the rest of the electromagnetic spectrum. Both classic and modern results are presented in a concise manner. After a brief discussion of the solar interior, the basic physics of the solar atmosphere and some elements of radiative transfer are presented. Subsequently the atmospheric structure as a function of height is examined and one-dimensional models of the photosphere, the chromosphere, the transition region and the corona are presented and discussed. An introduction to basic magnetohydrodynamics precedes the discussion of the rich fine structure of the solar atmosphere as a 3D object. Active regions are briefly discussed in a separate section, and this is followed by a section on the problem of heating of the chromosphere and the corona. I finish with some thoughts on what to expect from the new instruments currently under development.